Is it possible to deduce the ground state OH density from relative optical emission intensities of the OH(A2Σ+-X2Πi) transition in atmospheric pressure non-equilibrium plasmas?—An analysis of self-absorption. (13th July 2016) - Du, Yanjun; Peng, Zhimin; Ding, Yanjun; Sadeghi, Nader; Bruggeman, Peter J
Abstract: The measurement of absolute densities of reactive species and radicals such as OH is of growing interest for many plasma applications. In this paper, we extend the use of a self-absorption model for atomic emission spectroscopy to molecular emission spectroscopy. The proposed analysis of self-absorbed molecular emission spectra is a simple and inexpensive method to determine OH( X ) densities and rotational temperatures compared to laser induced fluorescence. We compare the recorded absolute OH density in a non-equilibrium diffuse atmospheric-pressure RF glow discharge by this method with broadband UV absorption considering a number of rotational lines with J ′  ⩽  6.5, the detection limit of the line integrated OH( X ) density with this method is of the order of 2  ×  10 19 m −2 . The accuracy of the density is sensitive to the rotational temperature of the OH( A ) state and the non-equilibrium rotational population distribution.